A relation between chronic rhinosinusitis with nasal polyps and COVID-19 course - E. V. Lyubimova; Elena L. Savlevich; A. V. Zurochka; Е. S. Mitrofanova (Инфекция и иммунитет)
The data on impact of chronic rhinosinusitis (CRS) on SARS-CoV-2 virus susceptibility and COVID-19 course were reviewed. CRS heterogeneity is determined by different types of inflammatory response. A heterogeneous CRS is divided into CRS without polyps and with nasal polyps (CRSwNP) is accounted for by diverse underlying immune responses. Hypersecretion of interleukins (IL)-4, IL-5, IL-13 in eosinophilic CRSwNP downmodulates angiotensin-converting enzyme (ACE)-2 receptor expression that should reduce SARS-CoV-2 infection risk because ACE2 is a main cellular tropism factor for SARS-CoV-2. In neutrophilic CRS type 1 immune response predominates, with activation of Th-1 cells, hypersecretion of interferon (IFN)-γ and tumor necrosis factor (TNF)-α to increase ACE2 expression. However, another data also show that hypoxemia level and pulmonary system damage did not differ between patients with CRS and CRS without polyps. Literature contradictions may be related to differences in availability of medical care, treatment of bronchial asthma (BA) as well as coverage of PCR testing. Regarding use of local or systemic glucocorticosteroids (GCS) effect on SARS-CoV-2 infection risk, some authors believe that GCS may increase COVID-19 severity and mortality, probably by downmodulating local innate immune response factors. According to other data, GCS may reduce ACE2 expression, or there is no relationship between previous GCS use, the incidence of COVID-19 and the frequency of treatment in the intensive care unit. Biological therapy of CRSwNP and BA with monoclonal antibodies did not aggravate COVID-19 severity and mortality risk. Although such data are currently limited, authors recommend not to interrupt such treatment during the epidemic, as well as continue taking leukotriene receptor blockers that can further inhibit major protease (Mpro) of the SARS-CoV-2 virus. However, according to international guidelines on COVID-19 treatment, using CRSwNP and asthma biological therapy should be discontinued until the patients recover completely. Allergen-specific immunotherapy (ASIT) should be interrupted in the case of confirmed COVID-19 due to a probability of developing severe COVID-19. After COVID-19, disturbances in the immune system may persist and possibly change the course of CRS, therefore requiring to modify therapeutic approaches for such patients. At the same time, the worldwide literature has been gradually accumulating information on pathogenesis underlying alterations in such patients including those with CRS, which requires development of new therapeutic approaches.